HEPATIC CANCER AND ITS RISK FACTORS IN NOVOSIBIRSK - O. V. Reshetnikov; T. G. Openko; S. A. Kurilovich; A. A. Khryanin; S. K. Malyutina (Сибирский онкологический журнал, 2016)
The dynamics of morbidity and mortality due to primary liver cancer in the population of Novosibirsk according to population cancer register and the total mortality over 25 years (1988-2012) as well as the levels of its risk factors were analyzed. There was a 2-2.5-fold reduction in morbidity and mortality from liver cancer. Among the risk factors, a significant reduction in the incidence of hepatitis B and increase in the incidence of hepatitis C were noted. Prevalence of metabolic syndrome, opisthorchiasis and alcohol consumption remain stable. The epidemiological prognosis for liver cancer in the coming years in the region is discussed.